Microporous titanium-gold film and method for manufacturing the same
Patent Information
- Application Number
- CN202610694684.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-20
- Publication Date
- 2026-10-09
AI Technical Summary
[0028]利用热塑性聚氨酯搭配热塑性聚酯弹性体、聚烯烃弹性体、乙烯-醋酸乙烯酯共聚物、热塑性硫化橡胶,进行高韧性、抗低温特性的互补改性。同时配合环保增塑剂弱化高分子链段作用力,提升树脂体系低温柔顺性,配合爽滑剂和分散剂保证材料混合的均匀性,避免低温分离和链段冻结硬化,并且利用纳米碳酸钙刚性颗粒支撑微孔、聚乙二醇亲水释孔的协同作用,实现透湿性与防钻绒性平衡。
Abstract
Description
Technical Field
[0001] This application relates to the field of titanium film production technology, specifically to a microporous titanium film and its preparation method. Background Technology
[0002] Currently, lightweight down jackets, close-fitting thermal clothing, and other textile fabrics generally require waterproof and breathable microporous membranes to achieve a combination of properties such as breathability, moisture permeability, down-proofing, and low-temperature resistance. Most existing microporous membranes on the market use a single thermoplastic polyurethane substrate formulation, which has the following drawbacks:
[0003] Conventional films use a dense structure to improve down-proof performance, which prevents moisture from escaping quickly, making the fabric stuffy and uncomfortable to wear. On the other hand, highly breathable structures are prone to down leakage, making it difficult to balance moisture permeability and down-proof performance. Moreover, thermoplastic polyurethane-based microporous films are prone to hardening and cracking in low-temperature environments, making them unsuitable for use in low-temperature outdoor scenarios. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this application solves the technical problem of how to achieve a balance between moisture permeability and downproofness while adapting to low-temperature outdoor scenarios.
[0005] To achieve the above objectives, embodiments of this application provide a microporous titanium film, the raw materials of which include, by weight:
[0006] Elastic substrate: 68-72 parts;
[0007] Composite pore-forming agent: 13-17 parts;
[0008] Nano-titanium modifier: 3-4 parts;
[0009] Environmentally friendly plasticizer: 6-8 parts;
[0010] Slip agent: 1.5-2.0 parts;
[0011] Antioxidant: 0.2-0.3 parts;
[0012] Dispersant: 0.1-0.2 parts.
[0013] In one embodiment, the elastic substrate comprises thermoplastic polyurethane and thermoplastic polyester elastomer, wherein the thermoplastic polyurethane and thermoplastic polyester elastomer are in a mass ratio of 47:24.
[0014] In one embodiment, the elastic substrate comprises thermoplastic polyurethane and polyolefin elastomer, wherein the thermoplastic polyurethane and polyolefin elastomer are in a mass ratio of 21:15.
[0015] In one embodiment, the elastic substrate comprises thermoplastic polyurethane and ethylene-vinyl acetate copolymer, wherein the thermoplastic polyurethane and ethylene-vinyl acetate copolymer are in a mass ratio of 51:21.
[0016] In one embodiment, the elastic substrate comprises thermoplastic polyurethane and thermoplastic vulcanized rubber, wherein the mass ratio of thermoplastic polyurethane to thermoplastic vulcanized rubber is 49:23.
[0017] In one embodiment, the composite pore-forming agent comprises nano-calcium carbonate and polyethylene glycol, and the mass ratio of nano-calcium carbonate and polyethylene glycol is 2-3:1;
[0018] The nano-calcium carbonate has a particle size of 50nm-80nm, and the polyethylene glycol is PEG-4000 or PEG-6000.
[0019] In one embodiment, the nano-titanium modifier is rutile nano-titanium dioxide with a surface modified by silane coupling agent KH-550, and its particle size is 20nm-30nm.
[0020] In one embodiment, the environmentally friendly plasticizer is tributyl acetylacetonate or epoxidized soybean oil;
[0021] The slip agent is erucamide or oleamide;
[0022] The dispersant is polyethylene wax with a molecular weight of 3000.
[0023] In one embodiment, the antioxidant includes antioxidant 1010 and antioxidant 168, and the antioxidant 1010 and antioxidant 168 are in a mass ratio of 1:1.
[0024] This application also provides a method for preparing a microporous titanium-gold film, the method comprising the following steps:
[0025] Add the elastic substrate to a high-speed mixer and premix at 85℃-95℃ for 8min-12min. Then add the composite pore-forming agent, nano titanium gold modifier, environmentally friendly plasticizer, slip agent, antioxidant and dispersant, and continue mixing for 12min-18min to obtain the mixture.
[0026] The mixture is added to a single-screw extruder. The temperature of the feeding section of the single-screw extruder is 160℃-170℃, the temperature of the plasticizing section is 175-185℃, the temperature of the homogenizing section is 185-195℃, the die temperature is 185-200℃, the blow-up ratio is 2.5-3.2, the draw ratio is 4.0-5.5, and the cooling air temperature is 20℃-25℃ to obtain a microporous titanium film.
[0027] Compared with the prior art, the advantages of this application are:
[0028] This study utilizes thermoplastic polyurethane in combination with thermoplastic polyester elastomers, polyolefin elastomers, ethylene-vinyl acetate copolymers, and thermoplastic vulcanized rubber to achieve complementary modifications in terms of high toughness and low-temperature resistance. Simultaneously, environmentally friendly plasticizers are added to weaken the polymer chain segment forces, improving the low-temperature flexibility of the resin system. Slip agents and dispersants are used to ensure uniform mixing of the materials, preventing low-temperature separation and chain segment freezing hardening. Furthermore, the synergistic effect of rigid nano-calcium carbonate particles supporting micropores and hydrophilic pores in polyethylene glycol achieves a balance between moisture permeability and down-proof properties. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] The embodiments of the present invention provide the following technical solutions:
[0031] Example 1
[0032] A microporous titanium film, the raw materials of which include, by weight:
[0033] Elastic substrate: 71 parts; the elastic substrate comprises thermoplastic polyurethane and thermoplastic polyester elastomer, and the mass ratio of thermoplastic polyurethane to thermoplastic polyester elastomer is 47:24; the thermoplastic polyurethane has a Shore hardness of 80A and a melt flow index of 18g / 10min (200℃ / 5.0kg); the thermoplastic polyester elastomer has a Shore hardness of 72D and a melting point of 190℃;
[0034] Composite pore-forming agent: 16 parts; The composite pore-forming agent includes nano calcium carbonate (particle size: 50nm-80nm) and PEG-4000 polyethylene glycol, and the mass ratio of nano calcium carbonate and PEG-4000 polyethylene glycol is 2:1;
[0035] Nano titanium modifier: 3.5 parts; The nano titanium modifier is rutile nano titanium dioxide with a surface modified by silane coupling agent KH-550, and its particle size is 20nm-30nm.
[0036] Acetyl tributyl citrate: 6.8 parts;
[0037] Erucamide: 1.7 parts;
[0038] Antioxidant: 0.25 parts; the antioxidant includes antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:1;
[0039] Polyethylene wax (molecular weight: 3000): 0.15 parts.
[0040] Based on this, the methods for preparing microporous titanium-gold films include:
[0041] Thermoplastic polyurethane and thermoplastic polyester elastomer were added to a high-speed mixer and premixed at 95°C for 8 minutes. Then, composite pore-forming agent, nano titanium gold modifier, acetylsalicylate tributyl ester, erucamide, antioxidant and polyethylene wax were added and mixed for another 12 minutes to obtain the mixture.
[0042] The mixture is added to a single-screw extruder. The temperature of the feeding section of the single-screw extruder is 160℃-170℃, the temperature of the plasticizing section is 175-185℃, the temperature of the homogenizing section is 185-195℃, the die temperature is 185-200℃, the blow-up ratio is 2.5-3.2, the draw ratio is 4.0-5.5, and the cooling air temperature is 20℃-25℃ to obtain a microporous titanium film.
[0043] Example 2
[0044] The difference between this embodiment and Example 1 is that the mass ratio of nano-calcium carbonate and PEG-4000 polyethylene glycol is 3:1.
[0045] Example 3
[0046] A microporous titanium film, the raw materials of which include, by weight:
[0047] Elastic substrate: 72 parts; the elastic substrate comprises thermoplastic polyurethane and polyolefin elastomer, and the mass ratio of thermoplastic polyurethane to polyolefin elastomer is 21:15; the thermoplastic polyurethane has a Shore hardness of 75A and a melt flow index of 20g / 10min (200℃ / 5.0kg); the polyolefin elastomer is an ethylene-octene copolymer with a density of 0.865g / cm³ and a melt flow index of 5g / 10min;
[0048] Composite pore-forming agent: 15 parts; The composite pore-forming agent includes nano calcium carbonate (particle size: 50nm-80nm) and PEG-6000 polyethylene glycol, and the mass ratio of nano calcium carbonate and PEG-6000 polyethylene glycol is 2:1;
[0049] Nano titanium modifier: 3 parts; The nano titanium modifier is rutile nano titanium dioxide with a surface modified by silane coupling agent KH-550, and its particle size is 20nm-30nm.
[0050] Epoxidized soybean oil: 7.5 parts;
[0051] Oleamide: 1.8 parts;
[0052] Antioxidant: 0.25 parts; the antioxidant includes antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:1;
[0053] Polyethylene wax (molecular weight: 3000): 0.15 parts.
[0054] Based on this, the methods for preparing microporous titanium-gold films include:
[0055] Thermoplastic polyurethane and polyolefin elastomer were added to a high-speed mixer and premixed at 85°C for 12 minutes. Then, composite pore-forming agent, nano titanium gold modifier, epoxidized soybean oil, oleic acid amide, antioxidant and polyethylene wax were added and mixed for another 18 minutes to obtain the mixture.
[0056] The mixture is added to a single-screw extruder. The temperature of the feeding section of the single-screw extruder is 160℃-170℃, the temperature of the plasticizing section is 175-185℃, the temperature of the homogenizing section is 185-195℃, the die temperature is 185-200℃, the blow-up ratio is 2.5-3.2, the draw ratio is 4.0-5.5, and the cooling air temperature is 20℃-25℃ to obtain a microporous titanium film.
[0057] Example 4
[0058] The difference between this embodiment and Example 3 is that the mass ratio of nano-calcium carbonate and PEG-6000 polyethylene glycol is 3:1.
[0059] Example 5
[0060] A microporous titanium film, the raw materials of which include, by weight:
[0061] Elastic substrate: 68 parts; the elastic substrate comprises thermoplastic polyurethane and ethylene-vinyl acetate copolymer, and the mass ratio of thermoplastic polyurethane to ethylene-vinyl acetate copolymer is 51:21; the thermoplastic polyurethane has a Shore hardness of 80A and a melt flow index of 16 g / 10 min (200℃ / 5.0 kg); the ethylene-vinyl acetate copolymer has a vinyl acetate content of 18% and a melt flow index of 2.5 g / 10 min;
[0062] Composite pore-forming agent: 17 parts; The composite pore-forming agent includes nano calcium carbonate (particle size: 50nm-80nm) and PEG-4000 polyethylene glycol, and the mass ratio of nano calcium carbonate and PEG-4000 polyethylene glycol is 2:1;
[0063] Nano titanium modifier: 4 parts; The nano titanium modifier is rutile nano titanium dioxide with a surface modified by silane coupling agent KH-550, and its particle size is 20nm-30nm.
[0064] Acetyl tributyl citrate: 6 parts;
[0065] Erucamide: 1.5 parts;
[0066] Antioxidant: 0.2 parts; the antioxidant includes antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:1;
[0067] Polyethylene wax (molecular weight: 3000): 0.1 parts.
[0068] Based on this, the methods for preparing microporous titanium-gold films include:
[0069] Thermoplastic polyurethane and ethylene-vinyl acetate copolymer were added to a high-speed mixer and premixed at 90°C for 10 min. Then, composite pore-forming agent, nano titanium gold modifier, acetylated tributyl citrate, erucamide, antioxidant and polyethylene wax were added and mixed for another 15 min to obtain the mixture.
[0070] The mixture is added to a single-screw extruder. The temperature of the feeding section of the single-screw extruder is 160℃-170℃, the temperature of the plasticizing section is 175-185℃, the temperature of the homogenizing section is 185-195℃, the die temperature is 185-200℃, the blow-up ratio is 2.5-3.2, the draw ratio is 4.0-5.5, and the cooling air temperature is 20℃-25℃ to obtain a microporous titanium film.
[0071] Example 6
[0072] The difference between this embodiment and Example 5 is that the mass ratio of nano-calcium carbonate and PEG-4000 polyethylene glycol is 3:1.
[0073] Example 7
[0074] A microporous titanium film, the raw materials of which include, by weight:
[0075] Elastic substrate: 69 parts; the thermoplastic polyurethane and thermoplastic vulcanized rubber, wherein the mass ratio of thermoplastic polyurethane and thermoplastic vulcanized rubber is 49:23; the thermoplastic polyurethane has a Shore hardness of 80A and is of hydrolysis resistant grade; the thermoplastic vulcanized rubber has a Shore hardness of 70A and is a blend of polypropylene and EPDM rubber.
[0076] Composite pore-forming agent: 13 parts; The composite pore-forming agent includes nano calcium carbonate (particle size: 50nm-80nm) and PEG-6000 polyethylene glycol, and the mass ratio of nano calcium carbonate and PEG-6000 polyethylene glycol is 2:1;
[0077] Nano titanium modifier: 3 parts; The nano titanium modifier is rutile nano titanium dioxide with a surface modified by silane coupling agent KH-550, and its particle size is 20nm-30nm.
[0078] Epoxidized soybean oil: 8 parts;
[0079] Oleamide: 2.0 parts;
[0080] Antioxidant: 0.3 parts; the antioxidant includes antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:1;
[0081] Polyethylene wax (molecular weight: 3000): 0.2 parts.
[0082] Based on this, the methods for preparing microporous titanium-gold films include:
[0083] Thermoplastic polyurethane and thermoplastic vulcanized rubber were added to a high-speed mixer and premixed at 90°C for 10 minutes. Then, composite pore-forming agent, nano titanium gold modifier, epoxidized soybean oil, oleic acid amide, antioxidant and polyethylene wax were added and mixed for another 16 minutes to obtain the mixture.
[0084] The mixture is added to a single-screw extruder. The temperature of the feeding section of the single-screw extruder is 160℃-170℃, the temperature of the plasticizing section is 175-185℃, the temperature of the homogenizing section is 185-195℃, the die temperature is 185-200℃, the blow-up ratio is 2.5-3.2, the draw ratio is 4.0-5.5, and the cooling air temperature is 20℃-25℃ to obtain a microporous titanium film.
[0085] Example 8
[0086] The difference between this embodiment and Example 7 is that the mass ratio of nano-calcium carbonate and PEG-6000 polyethylene glycol is 3:1.
[0087] Using the microporous titanium film raw material provided in the above embodiments, microporous titanium film was prepared, and samples 1, 2, 3, 4, 5, 6, 7, and 8 were obtained in sequence.
[0088] Samples 1-8 were tested for moisture permeability, down-proofness, and low-temperature brittleness. Specifically:
[0089] Moisture permeability is tested by sealing and fixing samples 1-8 on a moisture permeability cup under standard temperature and humidity conditions, letting them stand for 24 hours, weighing the water vapor permeation mass, and converting it into moisture permeability per unit area.
[0090] Downproof performance, the test method thereof is: using a standard friction testing machine, performing reciprocating friction for a specified number of times on samples 1 to 8 respectively, counting the total number of down and down filaments penetrating out from the surface of the sample, and the lower the value, the better the downproof performance:
[0091] Low temperature brittleness, the test method thereof is: placing samples 1 to 8 respectively in a low temperature chamber at -20°C for constant temperature standing for 2 hours, performing rapid impact bending, and the sample is qualified if it has no cracking, no whitening and no brittle fracture.
[0092] The test results are shown in Table 1:
[0093] Sample 1 ≥12500 ≤17 qualified Sample 2 ≥11000 ≤12 qualified Sample 3 ≥12000 ≤20 qualified Sample 4 ≥10500 ≤16 qualified Sample 5 ≥11800 ≤19 qualified Sample 6 ≥10200 ≤14 qualified Sample 7 ≥11500 ≤18 qualified Sample 8 ≥10000 ≤13 qualified
[0094] Table 1
[0095] It can be seen from Table 1 that the microporous titanium gold film provided by the present application has excellent moisture permeability, can quickly conduct out moisture from clothes, effectively block down filaments from penetrating out, has remarkable downproof performance, meets the application requirements of high-bulk down fabrics, and has excellent low temperature resistance. All samples have no brittle cracking, whitening or damage at the low temperature of -20°C, have excellent low temperature toughness, and can be adapted to low temperature use scenarios.
[0096] Further, when samples 1 to 8 are respectively composited with 7D-20D nylon, filament and polyester fabrics, a gluing compounding method is adopted, and the glue application amount is: 2.5-4g / m 2 , the compounding temperature is controlled at 45°C-60°C. Under this condition, it is found that the surface of the composited fabric has no obvious glue spots and has a skin-friendly touch when touched.
[0097] The terms "comprising" and "having" and any variations thereof in the description and claims of the present application are intended to cover non-exclusive inclusion. For example, a process, method, system, product or apparatus comprising a series of steps or units is not limited to the listed steps or units, but optionally further comprises steps or units not listed, or optionally further comprises other steps or units inherent to these processes, methods, products or apparatuses. The terms "first", "second" and "third" and other descriptions are used to distinguish different objects, etc., they do not represent an order, nor do they limit that "first", "second" and "third" are of different types.
[0098] In the description of the embodiments of the present application, "exemplary", "for example" or "by way of example" and other words are used to mean an example, illustration or description. Any embodiment or design solution described as "exemplary", "for example" or "by way of example" in the embodiments of the present application should not be construed as being more preferred or more advantageous than other embodiments or design solutions. To be precise, the use of words such as "exemplary", "for example" or "by way of example" is intended to present related concepts in a specific manner.
[0099] In the description of the embodiments of this application, unless otherwise stated, " / " means "or". For example, A / B can mean A or B. The "and / or" in the text is merely a description of the relationship between related objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist simultaneously, and B exists alone. In addition, in the description of the embodiments of this application, "multiple" means two or more.
[0100] In some processes described in the embodiments of this application, multiple operations or steps are included in a specific order. However, it should be understood that these operations or steps may not be executed in the order they appear in the embodiments of this application, or they may be executed in parallel. The sequence number of the operation is only used to distinguish different operations, and the sequence number itself does not represent any execution order. In addition, these processes may include more or fewer operations, and these operations or steps may be executed sequentially or in parallel, and these operations or steps may be combined.
[0101] The above are merely specific embodiments of this application, but the protection scope of this application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this application, and these modifications or substitutions should all be covered within the protection scope of this application. Therefore, the protection scope of this application should be determined by the scope of the claims.
Claims
1. A microporous titanium-gold film, characterized in that, Its raw materials, by weight, include: Elastic substrate: 68-72 parts; Composite pore-forming agent: 13-17 parts; Nano-titanium modifier: 3-4 parts; Environmentally friendly plasticizer: 6-8 parts; Slip agent: 1.5-2.0 parts; Antioxidant: 0.2-0.3 parts; Dispersant: 0.1-0.2 parts.
2. The microporous titanium-gold film according to claim 1, characterized in that, The elastic substrate comprises thermoplastic polyurethane and thermoplastic polyester elastomer, and the mass ratio of thermoplastic polyurethane to thermoplastic polyester elastomer is 47:
24.
3. The microporous titanium-gold film according to claim 1, characterized in that, The elastic substrate comprises thermoplastic polyurethane and polyolefin elastomer, and the mass ratio of thermoplastic polyurethane to polyolefin elastomer is 21:
15.
4. The microporous titanium-gold film according to claim 1, characterized in that, The elastic substrate comprises thermoplastic polyurethane and ethylene-vinyl acetate copolymer, wherein the thermoplastic polyurethane and ethylene-vinyl acetate copolymer are in a mass ratio of 51:
21.
5. The microporous titanium-gold film according to claim 1, characterized in that, The elastic substrate comprises thermoplastic polyurethane and thermoplastic vulcanized rubber, and the mass ratio of thermoplastic polyurethane to thermoplastic vulcanized rubber is 49:
23.
6. A microporous titanium-gold film according to any one of claims 1, 2, 3, 4, or 5, characterized in that, The composite pore-forming agent comprises nano-calcium carbonate and polyethylene glycol, and the mass ratio of nano-calcium carbonate and polyethylene glycol is 2-3:
1. The nano-calcium carbonate has a particle size of 50nm-80nm, and the polyethylene glycol is PEG-4000 or PEG-6000.
7. A microporous titanium-gold film according to any one of claims 1, 2, 3, 4, or 5, characterized in that, The nano-titanium modifier is rutile nano-titanium dioxide with a surface modified by silane coupling agent KH-550, and its particle size is 20nm-30nm.
8. A microporous titanium-gold film according to any one of claims 1, 2, 3, 4, or 5, characterized in that, The environmentally friendly plasticizer is tributyl acetylglucosyl citrate or epoxidized soybean oil; The slip agent is erucamide or oleamide; The dispersant is polyethylene wax with a molecular weight of 3000.
9. A microporous titanium-gold film according to any one of claims 1, 2, 3, 4, or 5, characterized in that, The antioxidants include antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1:
1.
10. A method for preparing a microporous titanium-gold film, characterized in that, The method includes the following steps: Add the elastic substrate to a high-speed mixer and premix at 85℃-95℃ for 8min-12min. Then add the composite pore-forming agent, nano titanium gold modifier, environmentally friendly plasticizer, slip agent, antioxidant and dispersant, and continue mixing for 12min-18min to obtain the mixture. The mixture is added to a single-screw extruder. The temperature of the feeding section of the single-screw extruder is 160℃-170℃, the temperature of the plasticizing section is 175-185℃, the temperature of the homogenizing section is 185-195℃, the die temperature is 185-200℃, the blow-up ratio is 2.5-3.2, the draw ratio is 4.0-5.5, and the cooling air temperature is 20℃-25℃ to obtain a microporous titanium film.